DETERMINANTS OF MERGERS AND ACQUISITIONS, A TOOL IN VUCA IN BUSINESS: A REVIEW STUDY - et al., Kanika Dhingra (International Journal of Advanced Science and Technology, 2019)
The business now-a-days is fetching a considerable and prosperous tool of the development of an economy, which laid its foundation at an unmatched position in the state. The financial growth of a country is vibrant from the steadiness of the business. Deregulation in the monetary market, markets getting liberalized, fiscal changes have observed surprising discrepancies in corporate resulting in implausible challenges and development of technology sovereignty in of late emerging phase of business. While every business is persistent in their efforts to grow into strong and operationally efficient model, thereby, one of the modes for achieving the same is through Mergers and Acquisitions. Mergers and Acquisitions is a terminology which is used for accomplishing higher progress with technical supremacy in markets and to attain international competitive advantage due to higher scale of operations leading to economies of scale. The objective of this research paper is to identify various factors affecting Mergers and Acquisitions in the Indian Business.The literature review in support of identifying the various determinants and impact of Mergers and Acquisitions is existing. This paper observes by analyzing the literature and theories available that determinants of Mergers and Acquisitions are diverse and they have impacted acquiring company in context of the value of firm, its prosperity, shareholders wealth, better return on equity thereby increasing the efficiency of the Organisation.